'On n'est pas condamné à l'échec': Hip-hop and the banlieue narrative. (August 2015) - Dotson-Renta, Lara
A number of contemporary French rappers such as Kery James, Médine and Youssoupha have reconfigured the artistic and societal image of the banlieue space and racial and religious otherness as 'also French' by undertaking a deconstruction of French identity and historical narratives. These musical artists, also predominantly Muslim, posit that the French model of cultural and religious assimilation actually precludes full societal integration: 'Mon respect s'fait violer au pays dit des droits de l'Homme / Difficile de se sentir français / Sans le syndrome de Stockholm' (Kery James, 'Lettre à la République'). Through lyrics that acknowledge marginalisation while also staking a claim to French identity, these artists displace concepts of centre and periphery by speaking to and about the nation from a space that is both within and outside the French national project. By challenging la laïcité as the only legitimate avenue to 'Frenchness' and insisting upon the quotidian urban banlieue narrative as that which also constitutes a genuinely 'French' experience, French Muslim rap artists have constructed an alternative discourse in which elements of society viewed as 'an/other' within France are reimagined as simultaneously disruptive and fundamentally constitutive of French national identity.